Perancangan Interior Restoran dan Edukasi Makanan Jepang di Surabaya - Melinda Chandra Susanto; mariana wibowo (Intra, 2016)
In the days of now the pattern and lifestyle society always following the trend. Gather is one of trend update, and restaurant is the target for them. Moreover, nowdays the peaople is very busy. They need something that could refresh theri minds as go on vacation abroad to enjoy the season. Therefore design with the concept of he season in the value of suitable. Beside, workshop as a food education area to make japanese food can be something unique in this restaurant. In this case, the design method used are data-accumulation method is done by literatures study about design, observation, and interview. Whereas the data-processing method is done by problems analysis, problem solving, programming, concept and schematic, and design development. The interviews and observations result shows that, trend, fact and concept become something important to facilitate what people's need and lifestyle.